Static and fatigue behaviours of a bolted GFRP/steel double lap joint. (January 2021) - Jiang, Zhengwen; Wan, Shui; Fang, Zhi; Song, Aiming
Abstract: To provide a safe and reliable connection using bolts for glass fibre-reinforced polymer (GFRP)/metal hybrid structures in civil engineering, the static and fatigue behaviours of a bolted GFRP/steel double-lap joint (DLJ) with a clamping force of 10 N m were investigated experimentally under monotonic tensile loading and repetitive tensile loading with a load ratio of R  = 0.1, respectively. The dominant failure modes, fatigue life and stiffness degradation law were obtained for the bolted DLJ. The fatigue damage evolution of the bolted DLJ was also clarified. The F–N curve and a non-linear stiffness degradation model were obtained from the experimental results for the bolted GFRP/steel DLJ. Finally, a comparison between the fatigue behaviour of the bolted GFRP/steel DLJ and that of a GFRP/GFRP DLJ was performed to identify the differences. The results indicated that the stiffness degradation law of the bolted GFRP/steel DLJ could be accurately characterized by the non-linear stiffness degradation model. The GFRP/steel DLJ exhibited a longer fatigue life than the GFRP/GFRP DLJ because the compressive stresses in the inner surface of the bolt-hole of the outer GFRP laminates were much smaller in the bolted GFRP/GFRP joint than the bolted GFRP/GFPR DLJ under the same applied maximum load. The stiffness degradation rate of the GFRP/steel DLJ under fatigue loading was almost the same as that of the GFRP/GFRP DLJ during their service lives. Highlights: Static and fatigue behavior of bolted DLJ with clamping force were studied. Fatigue damage evolution of bolted GFRP/steel DLJ was clarified. Stiffness degradation model applicable to bolted GFRP/steel DLJ was developed. Fatigue behavior of GFRP/steel DLJ was compared to that of GFRP/GFRP DLJ.